Analogy and Consensus in Ancient Arabic Sentence - Ghani Abdul-Ameer , Researcher. Zaineb; Prof. Dr. Ahmed Rasen Sahan , Prof. Dr. Ahmed (Basra studies journal, 2026)
This study examines analogy and consensus in ancient Arabic sentence compilations, as both analogy and consensus are considered fundamental principles of Arabic grammar, which relies on them to deduce the rules of Arabic sentence structure. The research explores the definition of analogy, its types, and its sources in sentence compilations. It also highlights the impact of analogy and consensus on formulating grammatical rules for Arabic sentences.